The Use of Smart TV Learning Media in Increasing Interest in Learning Islamic Cultural History in Elementary Madrasah - Dwi Winarno; Meti Fatimah (Didaktika: Jurnal Kependidikan, 2024)
This study aims to analyze the use of Smart TV learning media in increasing interest in learning the subject of Islamic Cultural History (SKI) at Madrasah Ibtidaiyah (MI) Gagaksipat 2. The approach used is qualitative with a case study method. The formulation of the problem raised in this study is how the use of Smart TV learning media can increase interest in learning SKI at MI Gagaksipat 2, and what are the positive impacts of its use. Data collection was carried out through observation, in-depth interviews, and documentation with teacher and student participants at MI Gagaksipat 2. The analysis method used is descriptive qualitative, namely data collection, data presentation, and conclusion. The results of the study indicate that the use of Smart TV as a learning medium can increase student interaction with SKI material, facilitate understanding of concepts, and enrich visual learning experiences. In addition, the use of Smart TV has proven effective in increasing student learning motivation, where students become more interested and enthusiastic in participating in learning. Other positive impacts are increased understanding of the subject matter and increased active participation of students in class. It can be concluded that Smart TV learning media plays a significant role in increasing interest in learning SKI at MI Gagaksipat 2, and provides a positive impact in the form of increasing student involvement in the learning process and better understanding of the subject matter.